The Effect of Organic Fertilizer of Fermented Rice Water with Different Doses in the culture of CholerellaSp. - Tarmizi, Tarmizi; Nuraini, Nuraini; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe research was conducted from August to September 2020 at the Waste Treatment Laboratory, Faculty of Fisheries and Marine, Riau University. The purpose of this study was to determine the effect of giving organic fertilizer as a result fermented of rice washing water on the culture of Clorella sp. and determine the best dosage of organic fertilizer from fermented rice washing water in the culture of Clorella sp. The research design was an experimental model using a completely randomized design with one factorial pattern (CRD) with 1 factor, 4 treatment and 3 replications. The treatment  used was AB0: 1 ml / L walne fertilizer (control), AB2: 2 ml / L rice washing water fertilizer, AB4: 4 ml / L rice washing water fertilizer, AB6: 6 ml / L rice washing water fertilizer. Cultivation wascarried out for 14 days. The results showed thatthe application of washing water fertilizer rice with different doses had an effect on population density and growth rate in cultures of Chlorella sp. The application of washing rice water fertilizer with a dose of 4 ml / L of water gave the best results with a maximum density of 600 x 104 cells / ml and a specific growth rate of 0.256 / day and the highest population peak on day 8. The results of water quality measurements during the study obtained temperatures of 28-31 0C, pH 7.3- 8.1, and DO 4-5 mg / L. Keywords: Clorella sp., Rice washing water, population density, growth rate